Validitas Bukti Digital dan Legalitas Penangkapan Pada Kasus Peretasan Akun Media Sosial Ravio Patra - Maharani, Nurrachma; Lamminar, Anatasia; Christiansen, Nicholas; Rafidah, Annisa Rahma; Nurrachman, Azzahra; Nugroho, Andriyanto Adhi (Media Hukum Indonesia (MHI), 2024)
Instant Messaging (IM) technology such as WhatsApp has grown rapidly, but it has also become a medium for cybercrime. This research examines the validity of digital evidence and the legality of arrest in the case of hacking the social media account of Ravio Patra, an activist accused of spreading provocation through WhatsApp after his account was hacked. Using a juridical-normative method, this research examines the types of digital evidence that are valid in Indonesia as well as aspects of the legality of arrests based on digital evidence. Relevant types of digital evidence include server log records, account activity, digital messages, and metadata. The validity of digital evidence is governed by the Electronic Information and Transaction Law (UU ITE) and the Criminal Procedure Code (KUHAP). Authentication processes are essential to ensure data integrity, but are often questioned due to the potential for manipulation. The Ravio Patra case shows the importance of legality in arrest and fair evidence collection. The identification of the actual perpetrator is crucial to prove the guilt or innocence of the accused. This research highlights the need for clear regulations and transparency in the management of digital evidence, as well as updates to legal regulations that are responsive to developments in information technology. Suggestions are given to strengthen regulations, ensure transparent processes, and provide regular training for law enforcement to handle digital evidence professionally and effectively